The department of economic adjustment : long-term macroeconomic global network strategies for changing the world : [an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts endorsed in Design at Massey University, Wellington, New Zealand] - Buchan-Ng, Monica (Massey University, 2014)
Welcome to the modal economy, where the diversity and fluidity of human nature is supported. We'd like to introduce a new economic system that encourages ethical, equitable behaviour through a series of improvements to the mechanisms of ownership, value, and trade. Capitalism has been with us for over 200 years, and it's time to upgrade. The modal economy will be implemented by supporting organisation The Department of Economic Adjustment. We look forward to engaging you through digital media, supplementary pamphlets, instructional videos, and a series of product development focus sessions. We are looking to make a dynamic and responsive economic structure in collaboration with you. Your feedback is important to us. What would you change about your economy?
Keywords: Economics in art; Capitalism in art